Composición taxonómica y abundancia espacio-temporal de la ictiofauna del Río Presidio, Sinaloa, México - Sánchez Gonzáles, Sergio; Ruiz Campos, Gorgonio; Herrrera Flores, Alejandro; Lozano Vilano, María de Lourdes; González Acosta, Adrián F.; Inzunza Beltrán, Héctor Manuel (2018)
Abstract: Taxonomic composition and spatio-temporal abundance of the ichthyofauna in Presidio River, Sinaloa, Mexico. The Rio Presidio in the southern Sinaloa, Mexico belongs to Nearctic-Neotropical zoogeographical transition zone, where its fish fauna could manifest changes in the abundance and distribution of the species during rainy and dry periods. The main objective of this study was to describe the taxonomic composition and spatial and temporal abundance of the fish fauna from the lower and middle Rio Presidio, by means of bimonthly samplings from April 2008 to February 2009. Forty fish species (39 native and 1 exotic) belonging to 32 genera and 19 families were registered. Two families (Gerreidae and Poeciliidae) contained the highest numbers of species (five and four, respectively). Six species (Lile stolifera, Oreochromis aureus, Awaous banana, Anchoa analis, Gobiomorus maculatus and Atherinella crystallina) in this order of importance contributed with almost 49 % of the total fish abundance. Species richness and salinity showed a direct relationship and an inverse relationship with the altitude. Based on the coefficient of similarity of species among sites two fish assemblages were identified. The first assemblage formed by species from marine derivation (peripheral) occurring in the lower part of the river, and the second assemblage by secondary freshwater species in the middle part. The higher fish species similarity observed in August and September was under the influence of the highest flows of the rainy period. Twenty-seven 27 species showed affinity to the Tropical Eastern Pacific Region, six species to the Neotropical region and two to the Nearctic region (Dorosoma smithi and Ictalurus cf. pricei ); one species has an Amphiatlantic distribution (Mugil curema), another is circumtropical (Mugil cephalus), two species have Amphiamerican distribution (A. monticola and G. cinereus), and one is exotic (O. aureus). Rev. Biol. Trop. 66(2): 848-862. Epub 2018 June 01. Key words: fish fauna; distribution; abundance; zoogeography; ecogeography.